2007
DOI: 10.2337/dc06-1772
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Endothelial Function Markers Before Conversion to Pre-Diabetes: Does the Clock Start Ticking Earlier Among Women?

Abstract: OBJECTIVE -We examined whether biomarkers of endothelial function, fibrinolysis/ thrombosis and adiponectin, predict the progression from normal to pre-diabetes more strongly among women than men over 6 years of follow-up from the Western New York Health Study. participants from the Western New York Health Study, who were free of type 2 diabetes and cardiovascular disease at baseline (1996 -2001), were selected for reexamination. An incident case of pre-diabetes was defined as fasting glucose Ͻ100 mg/dl at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 45 publications
(42 reference statements)
3
97
0
7
Order By: Relevance
“…The greater relative risk of CHD associated with diabetes in women may be explained by diabetes producing a more adverse change in the coagulation, inflammation and fibrinolytic system than men [14][15][16][17]; or, as explained above, changes in such pathways are simply greater due to a greater deterioration in insulin resistance in women. We examined several markers of inflammation that have been associated with diabetes and CHD including CRP, IL-6 and WBC [13,23], and all showed differing patterns of associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater relative risk of CHD associated with diabetes in women may be explained by diabetes producing a more adverse change in the coagulation, inflammation and fibrinolytic system than men [14][15][16][17]; or, as explained above, changes in such pathways are simply greater due to a greater deterioration in insulin resistance in women. We examined several markers of inflammation that have been associated with diabetes and CHD including CRP, IL-6 and WBC [13,23], and all showed differing patterns of associations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent attention has turned to emerging CV risk factors including endothelial dysfunction, inflammation and fibrinolysis, which have been associated with diabetes risk [13]. Women with type 2 diabetes may be subject to even more adverse changes in coagulation, inflammation and vascular function than men [14][15][16][17]. Insulin resistance, a recognised contributor to hyperglycaemia and diabetes precedes the development of diabetes by years and has been associated with increased CVD risk including dyslipidaemia, hypertension, impaired fibrinolysis, inflammation and coagulation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the difference in both traditional and novel cardiovascular risk factor levels in people with and without diabetes is significantly greater in women than in men [26][27][28][29][30][31][32]. Furthermore, in the prediabetic state where glucose tolerance may already be impaired but does not meet all diagnostic criteria of diabetes, risk factor levels are more elevated in women than in men [33,34]. Several studies have suggested that men develop diabetes at a lower BMI compared with women [32,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the cause-effect relationships observed in cross sectional studies may be confounded by unknown variables. 44 Donahue et al 45 showed that women who progress from normoglycemia to prediabetes have greater endothelial dysfunction, a greater degree of fibrinolysis/thrombosis, and are more hypertensive than men. 45 It has been shown that women with hypertension have a higher prevalence of other concomitant cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%